Exponentiated–Exponential Logistic Distribution: Some Properties and Application - Sapkota, Laxmi Prasad (Janapriya Journal of Interdisciplinary Studies, 2020)
This study proposes new distribution which is generated from exponentiated-exponential-X family of distribution. It is explored various shape and behavior of the observed distribution through probability density plot, hazard rate function and quantile function. Further we have investigated some mathematical properties, estimation of the parameters and associated confidence interval using maximum likelihood estimation (MLE) method of the exponentiatedexponential-logistic distribution (EELD).